Neuroaesthetics 2.0: On the Internal Evolution of the Naturalistic Approach in Art Research - Przybysz, Piotr (Sensus Historiae, 2023)
The attempt of neuroaesthetics to answer questions about the “centers of beauty” in the brain and the mechanisms that govern the multi-stage perceptual process of artworks turned out to be insufficient to explain human aesthetic competence. Therefore, in the new version of this project, which I refer to as “Neuroaesthetics 2.0,” a decision was made to correct the initial assumptions of neuroaesthetics. It has also been recognized that neuroaesthetics should place greater emphasis on revealing the connections between beauty and other aesthetic categories, consider the context of art reception more extensively, and acknowledge the significant role of meaning and contextual knowledge, as well as aesthetic evaluation, in the formation of aesthetic experience. In the paper, I try to answer the question of what new Neuroaesthetics 2.0 brings to neuroscientific research on art cognition.